Pemanfaatan Sistem Klasifikasi dan Selving Bahan Pustaka: Upaya Memenuhi Temu Kembali Informasi di Perpustakaan Politeknik Negeri Sriwijaya - Fitriah, Sonya Nur; Rosita, Wiwid; Rohmaniyah, Rohmaniyah (UIN Raden Intan Lampung, 2022)
This article discusses the Utilization of an Effective Classification and Shelving System for Library Materials in Meeting Information Retrieval Needs at UPT. Sriwijaya State Polytechnic Library. The purpose of this study was to determine the use of a classification system and an effective shelving of library materials in meeting the needs of information retrieval at UPT. Sriwijaya State Polytechnic Library and how effective the use of alphabetical shelving is to facilitate the information retrieval system. The research method in this article is a type of qualitative descriptive research. Qualitative descriptive research is research that aims to describe a situation or event in the way it is. The result of the analysis in this article is the determination of the classification number based on the subject and the predetermined chart. If you can analyze the subject correctly and can follow the instructions on the classification chart, you are expected to get the right subject and get the right notation. So that the placement of library materials on the shelves in the correct position and the information retrieval system along with the process of searching or searching for information is easy to do quickly and precisely. Shelving process carried out at UPT. The Sriwijaya State Polytechnic Library for general works refers to the classification number on a regular basis and is matched with the classification number provided on each bookshelf.